Respuesta :
14y - 4 = 24y + 26
-4 - 26 = 24y - 14y
-30 = 10y
10y = -30
y =- -30/10
y = -3
12y =12(-3)
12y = -36
-4 - 26 = 24y - 14y
-30 = 10y
10y = -30
y =- -30/10
y = -3
12y =12(-3)
12y = -36
Solutions
To solve the equation we have to isolate 12y
[tex]14y - 4 = 24y + 26 -4 - 26 = 24y - 14y -30 = 10y 10y = -30 y =- -30/10 y = -3 12y =12/-3 12y = -36 Therefore, 12y = -36[/tex]
To solve the equation we have to isolate 12y
[tex]14y - 4 = 24y + 26 -4 - 26 = 24y - 14y -30 = 10y 10y = -30 y =- -30/10 y = -3 12y =12/-3 12y = -36 Therefore, 12y = -36[/tex]